Strategi Pemasaran Digital Untuk Meningkatkan Penjualan UMKM Di Desa Sembulung Banyuwangi - wijaksono, agus; Wapa, Andi; Hidayat, Imam (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Sembulung Village face challenges in enhancing their competitiveness and business sustainability in the digital era. These challenges include limited understanding and skills in utilizing digital platforms for effective product marketing. This community service aims to provide practical and applicable solutions through the implementation of relevant digital marketing strategies. The program also analyzes the potential of local products with high market value and strategies for optimizing digital platforms to reach a broader audience. The results are expected to significantly impact the increase in MSME product sales and local economic growth. Furthermore, this initiative contributes as a reference for MSME actors and related stakeholders in strengthening business competitiveness amidst the global marketing landscape transformation